PENGARUH PELATIHAN KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT MAAQO JOMBANG - Nur Fadilah ATI (Jurnal Ilmiah Manajemen dan Bisnis, 2020)
PT MAAQO Jombang is an industriall compny thats poduces botted dringking water in jombang. This studiy aims to determine wheater or not the influence of job training and work discipline on the work productivity of employees at PT MAAQO. Thes type of reseearch ussed  this studiy iquantitative reseaarch with an associative approach. The sampling  technique used was saturated samples with a sample of 76 employees at PT MAAQO. This sudy uses the technique of collecting data on obsevations, interviews, questionnaires an documentation. Datanalysis techniiques ussed are multipple liner regressions analisis, t test and f test with results.